The determinants of unemployment across OECD countries Reassessing the role of policies and institutions - Bassanini, Andrea (OECD Publishing, 2007)
Andrea Bassanini and Romain Duval are economists at the Directorate for Employment, Labour and Social Affairs and the OECD Economics Department, respectively. Catherine Chapuis-Grabiner, Sébastien Martin and Rebecca Oyomopito provided excellent research assistance. Comments from Sveinbjorn Blöndal, Wendy Carlin, Jean-Philippe Cotis, Martine Durand, Jorgen Elmeskov, Michael P. Feiner, David Howell, Etienne Lehmann, Edmond Malinvaud, John P. Martin, Giuseppe Nicoletti, Stefano Scarpetta, Paul Swaim, Raymond Torres and participants to the joint WP1/WP5 EPC-ELSAC meeting in Paris, January 2006, and the Séminaire Fourgeaud, Paris, May 2006, are also gratefully acknowledged. Any errors are the responsibilities of the authors alone. The views expressed in this paper are those of the authors, and do not necessarily reflect those of the OECD or of its member countries
Keywords: Economics